(3JYde (BORACLE 10g-PL/SQLs ((3GdbGgQIs Pc lab, 2007)
(3Sha fJYQa aj gPG GdeSJhj ef GdeLehYI GdJYdjejI dfJYde (BORACLE 10g(3Ydj dZI GdHQeLI Ydj dZI GdHQeLI dEfTGA JWHjbGJ bhGYO GdHjGfGJ hGdhUhd Edj HjGfGJ bhGYO GdHjGfGJ heYGdLJgGs
1 2 3 12
Keywords: ORACLE -- (3ehGO SeYjI hHUQjIs; (3GdMGSHGJ GdEdcJQhfjIs -- (3JYdjes -- (3ehGO SeYjI hHUQjIs; (3bhGYO GdHjGfGJs -- (3JUejes -- (3ehGO SeYjI hHUQjIs; (3eGdJj ejOjGs -- (3cHGQs -- (3ehGO SeYjI hHUQjIs